Difference between revisions of "2006 Alabama ARML TST Problems/Problem 13"
(→See also) |
m (→Solution) |
||
Line 17: | Line 17: | ||
<math>\sqrt[4]{x+27}=3\Rightarrow x=54, \sqrt[4]{55-x}=1</math> | <math>\sqrt[4]{x+27}=3\Rightarrow x=54, \sqrt[4]{55-x}=1</math> | ||
− | Another solution. But we see that <math>54-26=55-27</math>. So we try to prove that if <math>y</math> is a solution, then <math>28-y</math> is a solution: | + | Another solution. But we see that <math>54-26=55-27=28</math>. So we try to prove that if <math>y</math> is a solution, then <math>28-y</math> is a solution: |
<math>\sqrt[4]{y+27}+\sqrt[4]{55-y}=4</math> | <math>\sqrt[4]{y+27}+\sqrt[4]{55-y}=4</math> |
Revision as of 15:37, 17 April 2008
Problem
Find the sum of the solutions to the equation
![$\sqrt[4]{x+27}+\sqrt[4]{55-x}=4.$](http://latex.artofproblemsolving.com/1/8/9/1897a39814976cd4572a611ef31e56b0e4b88c34.png)
Solution
There are four solutions, since we have fourth roots. We try to find some nice solutions:
Not quite, but
That's a solution! Now we switch:
Another solution. But we see that . So we try to prove that if
is a solution, then
is a solution:
We plug in for y and we get
But that just equals four! Thus, if is a solution, then
is a solution.
Since there are four roots,
See also
2006 Alabama ARML TST (Problems) | ||
Preceded by: Problem 12 |
Followed by: Problem 14 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 |